2019
DOI: 10.36109/rmg.v158i1.124
|View full text |Cite
|
Sign up to set email alerts
|

Osteoartrosis de rodilla. Tratamiento con plasma rico en plaquetas. Reporte de 29 casos

Abstract: La osteoartrosis de la rodilla es una enfermedad crónica con una alta prevalencia a nivel mundial. A medida que las poblaciones envejecen el número de afectados aumenta, alterando en diversos grados la calidad de vida. El tratamiento de esta enfermedad ha sido difícil y no está exento de efectos colaterales que pueden ser peligrosos. Por su cronicidad requiere de tratamientos prolongados que potencializan los efectos colaterales y elevan los costos. La aplicación de plasma rico en plaquetas en la cavidad artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…Osteoarthrosis of the knee is a chronic disease with a high prevalence worldwide. As populations age, the number of people affected increases, altering the quality of life to various degrees [1]. In recent years, especially in developed countries, the increase in life expectancy has been observed, but with the prevalence and incidence of diseases of the elderly has also increased.…”
Section: Short Communicationmentioning
confidence: 99%
“…Osteoarthrosis of the knee is a chronic disease with a high prevalence worldwide. As populations age, the number of people affected increases, altering the quality of life to various degrees [1]. In recent years, especially in developed countries, the increase in life expectancy has been observed, but with the prevalence and incidence of diseases of the elderly has also increased.…”
Section: Short Communicationmentioning
confidence: 99%
“…Osteoarthrosis (OA) or gonoarthrosis of the knee is a chronic disease with a high prevalence worldwide. As populations age, the number of affected increases, altering quality of life to varying degrees [1]. To determine the exact prevalence of knee OA, the definition of the disease used, the diagnostic method (clinical and/or imaging), and the affected joint are essential, for which reason the available data are diverse.…”
Section: Short Communicationmentioning
confidence: 99%
“…Another variant of conservative treatment is the application of plasma rich in growth factors, in studies carried out by different authors it was shown that it is an effective and safe procedure; with which only mild complications are recorded [1,5]. Before reaching a large and expensive surgical intervention, plateletrich plasma is a treatment of choice in gonoarthrosis for the improvement of symptoms, although it does not eliminate the disease.…”
Section: Short Communicationmentioning
confidence: 99%
“…Guatemala, al ser un país multiétnico, multilingüe y multicultural, no tiene estudios que evalúen el espectro total de enfermedades MSK [6]. Los datos disponibles en el país son limitados [6][7][8].…”
Section: Introductionunclassified